Complete Mitochondrial Complex I Deficiency Induces an Up-Regulation of Respiratory Fluxes That Is Abolished by Traces of Functional Complex I. Issue 4 (1st July 2015) - Kühn, Kristina; Obata, Toshihiro; Feher, Kristen; Bock, Ralph; Fernie, Alisdair R.; Meyer, Etienne H.
Abstract : Respiratory chain complex I acts as a negative regulator of fluxes through glycolysis and the TCA cycle. Abstract: Complex I (NADH:ubiquinone oxidoreductase) is central to cellular NAD + recycling and accounts for approximately 40% of mitochondrial ATP production. To understand how complex I function impacts respiration and plant development, we isolated Arabidopsis ( Arabidopsis thaliana ) lines that lack complex I activity due to the absence of the catalytic subunit NDUFV1 (for NADH:ubiquinone oxidoreductase flavoprotein1) and compared these plants with ndufs4 (for NADH:ubiquinone oxidoreductase Fe-S protein4 ) mutants possessing trace amounts of complex I. Unlike ndufs4 plants, ndufv1 lines were largely unable to establish seedlings in the absence of externally supplied sucrose. Measurements of mitochondrial respiration and ATP synthesis revealed that compared with ndufv1, the complex I amounts retained by ndufs4 did not increase mitochondrial respiration and oxidative phosphorylation capacities. No major differences were seen in the mitochondrial proteomes, cellular metabolomes, or transcriptomes between ndufv1 and ndufs4 . The analysis of fluxes through the respiratory pathway revealed that in ndufv1, fluxes through glycolysis and the tricarboxylic acid cycle were dramatically increased compared with ndufs4, which showed near wild-type-like fluxes. This indicates that the strong growth defects seen for plants lacking complex I originate from a switch in the metabolic mode of mitochondria and an up-regulation of respiratory fluxes. Partial reversion of these phenotypes when traces of active complex I are present suggests that complex I is essential for plant development and likely acts as a negative regulator of respiratory fluxes.